Deep sequencing shows that HBV basal core promoter and precore variants reduce the likelihood of HBsAg loss following tenofovir disoproxil fumarate therapy in HBeAg-positive chronic hepatitis B. Issue 11 (17th August 2016) - Bayliss, Julianne; Yuen, Lilly; Rosenberg, Gillian; Wong, Darren; Littlejohn, Margaret; Jackson, Kathleen; Gaggar, Anuj; Kitrinos, Kathryn M; Subramanian, G Mani; Marcellin, Patrick; Buti, Maria; Janssen, Harry L A; et al.
Abstract : Objective: Hepatitis B e antigen (HBeAg) seroconversion and hepatitis B surface antigen (HBsAg) loss are important clinical outcomes for patients with chronic hepatitis B (CHB) treated with antiviral therapy. To date, there have been few studies that have evaluated viral sequence markers predicting serological response to nucleos(t)ide analogue (NA) treatment. Design: We used next-generation sequencing (NGS) and quantitative HBV serology (HBeAg and HBsAg) to identify viral sequence markers associated with serological response to long-term tenofovir disoproxil fumarate therapy among HBeAg-positive patients. In the GS-US-174-0103 study, approximately half the patients seroconverted to anti-HBe by week 192 and 11% of patients exhibited HBsAg loss, the closest outcome to functional cure. The frequency of HBV variants that have previously been associated with HBV clinical outcomes was evaluated. HBV viral diversity in baseline sequences generated by NGS was calculated using Shannon entropy. Results: NGS analysis of HBV sequences from 157 patients infected with genotypes A to D showed the frequency of variants in the basal core promoter (BCP) and precore (PC) regions varied by genotype and that these mutations were associated with the absence of HBsAg loss. This was the case even when mutations were present at frequencies below the threshold of detection by population sequencing. Increased viral diversity across the HBV genome as determined by NGS was also associated with reduced likelihood of HBsAg loss. Conclusion: Patients with detectable BCP and/or PC variants and higher viral diversity have a lower probability of HBsAg loss during long-term NA therapy. Strategies to achieve functional cure of HBV infection through combination therapy should consider using NGS to stratify patients according to BCP/PC sequence. Consideration should also be given to earlier initiation of therapy prior to the emergence of BCP/PC variants. Trial registration number: NCT00116805; Post result.